Neurodegeneration and neuroprotection in Parkinson's disease - Olanow, C. W; Jenner, Peter; Youdim, Moussa B. H (Academic Press, 1996)
Neuroscience Perspectives provides multidisciplinary reviews of topics in one of the most divers and rapidly advancing fields in the life sciences. Whether you are a new recruit to neuroscience, or an established expert, look to this series for \'one-stop\' sources of the historical, physiological, pharmacological, biochemical, molecular biological, and therapeutic aspects of chosen research areas.
Neuroscience perspectives
Keywords: Nerve Degeneration; Aluminum; degenerace nervu; hliník; Parkinsonova nemoc; neurovědy; Iron; železo; Parkinson Disease; neurologie